Uji Efektivitas Ekstrak Etanol Daun Jambu Mete (Anacardium occidentale L.) Sebagai Analgetik Pada Tikus Putih (Rattus norvegicus) - Rahmat Ismail; Hamidah Sri Supriati; Nurul Hastuti Raun (Jurnal Sains dan Kesehatan, 2020)
Pain is a defense mechanism of the body and caused by tissue damage to the body due to injury, accident or medical action. Traditionally, cashew leaves were used in curing inflammation, pain, toothache, wound healing, rheumatism as well as dysentery. This study aims to determine the effectiveness of analgetic power of cashew leaf ethanol extract (Anacardium occidentale L.) in white rats (Rattus norvegicus). The research conducted is experimental research, with chemical excitatory methods. The test animals were divided into 5 groups with each treatment of 3 mice. Group I Na CMC 1%, group II Paracetamol, group III cashew leaf ethanol extract 10%, group IV cashew leaf ethanol extract 20%, and group V cashew leaf ethanol extract 40% given orally. Pain inductors are 1% induced acetic acid intraperitonially. Observed the amount of mice geliat for 1 hour and calculated percent analgetic power. The results obtained in this study have properties as analgetics with analgetic power concentration of 10%: 82.73%, concentration of 20%: 84.89%, and concentration of 40%: 88.48%.